Currently available technologies for continuous sodium monitoring in plasma or interstitial fluid: A scoping review - Yu Zhang; Hanneke M. van Santen; Ruben E.A. Musson; Panos Markopoulos; Yuan Lu (Sensing and Bio-Sensing Research, 2025)
The human body maintains plasma sodium concentration within a narrow range of 135 to 145 mmol/L to ensure homeostasis. Being outside this range denotes hyponatremia (below 135 mmol/L) or hypernatremia (above 145 mmol/L), which can cause serious health problems. Current sodium monitoring is performed using point-of-care devices, which require blood sampling every time. It is cumbersome and uncomfortable for patients who require frequent sodium measurements daily. It would be ideal to continuously monitor plasma sodium concentration to reduce burden and detect abnormalities earlier. The sodium concentration in interstitial fluid is close to plasma sodium. Thus, this scoping review presents the current technological developments for continuous sodium monitoring (CSM) in plasma or interstitial fluid. The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR) checklist. 11 articles that presented technologies for the continuous monitoring of sodium concentrations in plasma or interstitial fluid with at least a technology readiness level of four were included for review. Seven of them presented microneedle(MN)-based solutions for CSM, and the remaining four were fluorescence(FS)-based. MN-based sodium sensors are all-solid-state sodium ion-selective electrodes designed as MN arrays or standalone MNs. FS-based CSM technologies inject sodium-sensitive fluorophores into the bloodstream or subcutaneously to reflect local sodium concentrations. Comparison of these two technological paths based on expected patient experience revealed that MN-based technologies appear more feasible for daily use and promising for further development due to their minimal invasiveness and compact wearability.